Palm Leaf as a Thermal Insulation Material - AL-Nesearawi, M. A.-N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper presents calculat,ion of thermal conductivity (K) of palm leaf experimentally using Lee s disc method to be used as thermal insulator. The therma l conducti vity is found to be equal to (k=0.03W/mK) indicating that palm l eaf is a good thermal insulator com pared to the other insulators. The effect of the thermal insulator thickness on temperature di lTt::rence, heat transfer coefficient, thermal conductance, thermal resistance, thermal insulation are in vestigated in this paper. It was found that i ncreasi ng thickness of the good i nsulator (such as palm !eat) leads to increasing both thermal resistance and insulation while decreasing both heat transfer coefficient and thermal conductance until specific point wh ich after it they are not affected by thickness (they being constant).